Effect of The Resuscitation Training Program on Knowledge and Skills and Perceived Self-Efficacy of Resuscitation Village Health Volunteers in Khlong Chik Subdistrict, Bang Pra in District, Phra Nakhon Si Ayutthaya Province - Sasang, Natnapa; Chusak, Thassaporn; Sanee, Aree (Journal of The Royal Thai Army Nurses, 2020)
The study of the effect of the resuscitation training program on knowledge and skills And perceived self-efficacy in resuscitation of Village health volunteers in Khlong Chik Subdistrict, Bang Pa-in District Phra Nakhon Si Ayutthaya The purpose is to compare knowledge. Skills and perceptions of self-efficacy in resuscitation of Village health volunteers before-after receiving resuscitation training programs Materials and methods This research is conducted by conducting experiments on existing samples. There was no random sampling and measurement before - after the experiment. The sample consisted of village health volunteers in Khlong Chik Subdistrict Municipality. Bang Pa-in Phra Nakhon Si Ayutthaya Who had never been trained in resuscitation The sample number is 50 people, which is obtained by selecting a specific sample group. The tools used in this research were Test of knowledge about resuscitation With a reliability of 0.82 and the assessment of resuscitation skills With a reliability of 0.86. The self-efficacy assessment form for resuscitation With confidence value 0.78. The statistics used in Data analysis is frequency distribution, percentage, mean, standard deviation. And comparing with the two types of T values is not independent from one another The results showed that after receiving the resuscitation training program The knowledge and skills of Village health volunteers regarding resuscitation had a higher average score than before receiving the program with statistical significance at the level of .05 and the perceived self-efficacy of basic resuscitation of Village health volunteers. It was found that after receiving the resuscitation training program, the mean score was higher than before receiving the program at the statistical significance level of .05. Conclusion The resuscitation training program is necessary and important in helping develop potential, increasing confidence in the performance of duties. Able to help people with cardiac arrest in emergency situations before being hospitalized